Development of Educational Game-assisted Accounting Learning Media based on Role-Playing Game to Improve Students' Analytical Abilities - Sitompul, Dian Novianti; Dongoran, Faisal Rahman; Fitri, Harningsih (Universitas Pendidikan Mandalika, 2025)
This study aims to develop educational game-assisted accounting learning media based on role playing game to improve students' analytical abilities. This study uses the Research and Development (R&D) method with the ADDIE model with 32 students as research subjects. The data collection technique used is a questionnaire in the form of a validation sheet, a student response questionnaire, and a test sheet to measure the effectiveness of the media. The data analysis technique used is a descriptive technique. The results of this study showed that the educational game learning media developed is valid with an average score from media experts of 88%. Furthermore, the study of student questionnaires showed a positive reaction of 90% practical and effective with N.Gain 80. This study concludes that educational game media can improve students' analytical skills, especially on the subject of bank reconciliation.